Influence of the Enochic tradition on Qumran: reception and adaptation of the Watchers and Giants as a case study - Juan Sebastián Hernández Valencia (Perseitas)
The confluence of different Jewish traditions in the Qumran library is evident. The Enochic traditions are not only counted as the oldest influences in Qumran, they also give it a certain theological unity. This is even more true in the case of demonology. Belial’s figure brings together a rich lexicographic heritage in which different traditions are integrated under the characteristics of the Watchers and Giants of the Enochic tradition (1 En 6—8). This study analyzes the theological characterization of the demonological figures found in Qumran to specify the Enochic influence on it.